Evaluation of the impact strength of the traction gearbox housing for the traction of a high-speed electric train in terms of deformation rate of the material - E. K. Rybnikov; S. V. Volodin; T. O. Vakhromeeva (Вестник Научно-исследовательского института железнодорожного транспорта, 2023)
Introduction. Solving a wide range of problems to maintain the strength of train undercarriage under the impact of ballast particles, such as ice chunks, during the cold season is considered a topical issue for high-speed railways. Solid objects are lifted off the track surface as a result of aerodynamic interaction with the turbulent airflow of a high-speed train. This causes mechanical damage to the bogie and its components, which could be significant and endanger road safety. The aim of this study is to assess the probability of significant damage to the traction gearbox housing from foreign objects on the way and to develop a method of protection.Materials and methods. Housing failure potential is calculated using numerical simulation in MSC.Nastran_SOL700 environment, allowing analysis of short duration dynamic events with severe geometry and material non-linearity. The method of assessment of the structural strength of a traction gearbox housing under the dynamic action of a foreign object is described.Results. The calculation methodology is tested on a simplified traction gearbox housing model. The methodology is then applied to models that are close to the real traction gearbox housing. The General model and the Cowper — Simonds model, which incorporates the strain rate dependence of the dynamic deformation of the material, are considered for specifying the material properties. The effect of foreign objects of different masses and relative speed on the probability of damage to the traction gearbox walls at different thicknesses is assessed.Discussion and conclusion. Calculations confirm the probability of destruction of housings of traction gearboxes of high-speed and high-speed electric trains under the dynamic impact on the body of third-party objects. Structural solutions for protecting housings of traction gearboxes of high-speed trains from the effects of foreign objects are analysed and the most rational option is chosen. This article was written based on the authors' paper presented at the XXII Russian MSC Software Conference (HxGN Live Design & Engineering Russia 2021), November 16-19, 2021.